The prognostic ability of curb-65 in predicting outcomes of hospitalised patients with community acquired pneumonia in Hospital Universiti Sains Malaysia - Abdul Razak, Nurul Majidah (2015)
Background Community Acquired pneumonia (CAP) is a common disease and many patients require admission, which is about 20-40% of patients. It also has high morbidity and mortality. CAP still remains one of the leading causes of death from infectious diseases. There are several validated tools to assess severity, predict mortality in patients admitted with CAP and guide clinical decision about the level of intervention required for better monitoring and treatment. The purpose of this study is to determine the prognostic ability of CURB-65 as a pneumonia severity score in predicting outcomes in hospitalized patients with CAP. Methodology The study was an observational retrospective cohort study performed for patients admitted to medical ward and intensive care unit (ICU) HUSM that fulfilled diagnosis for CAP, from June 2012 till May 2014. The clinical profiles for CAP in HUSM were elaborated in a descriptive study. The adverse outcomes that were investigated in this study were use of inotropic support, need of ventilation support, ICU admission and in hospital mortality. The prognostic ability of CURB-65 in predicting outcomes were analysed using 4 tests, i.e: Chi square test, SLR, ROC curve analysis and sensitivity, specificity and predictive values. The recommended cut off points to indicate higher CURB-65 score was 3 to 5. Results The majority of patients were Malay (95.4%) with almost equal male to female distribution and mean age of 63.29 (SD+16.55) years. The proportion of in hospital xvii mortality was 8.8%, use of inotropic support was 11.1% , need of ventilation support was 12.6% and need of ICU admission was 6.9%. CURB-65 score severity category demonstrated high sensitivity (89-100%), specificity (84-88%), negative predictive value (99-100%) and area under ROC curve; and significant association with all the adverse outcomes. It also had good to excellent discriminative values (0.853-0.938). Conclusion Our study showed CURB-65 had a prognostic ability in predicting outcomes i.e: used of inotropic support, need of ventilation support, need of ICU admission and inhospital mortality for hospitalised patients with community acquired pneumonia with high sensitivity and specificity.